Informal Science Contexts: Implications for Formal Science Learning (LEARNing Landscapes, 2012)
This article illuminates the affordances of informal science learning to promote scientific literacy. It also discusses the ways in which informal learning environments can be creatively employed to enhance science instruction in K-12 as well as university settings. Also offered are various theoretical perspectives that serve as useful analytical tools to understand science learning in formal as well as informal settings.
Keywords: informal science learning; scientific literacy; informal learning environments; K-12; inforaml learning